A carbon nanotube / platinum-coated titanium carbide composite material and its preparation method and application

By using carbon nanotube/platinum-coated titanium carbide composite materials to modify screen-printed electrodes to form a three-dimensional conductive network structure, it solves the problem of difficulty in detecting the content of indole acetic acid in plants in the existing technology and achieves efficient and stable electrochemistry. detection.

CN118811818BActive Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411265989.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-24
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently detect the content of indole acetic acid in plants, especially when its content is too low and the electroactive substance is small.

Method used

Use carbon nanotuba/platinum titanium titanium titanium composite material, use it to modify the screen printing electrodes, connect the hydrogen bonds between carbon nanotubes and titanium carbide nanoscope, and platinum nanoparticles loaded on the surface of the carbon nanotuba. Form the three -dimensional conductivity network structure, thereby improving electrochemical signals and stability.

Benefits of technology

The electrochemical signal and stability are significantly improved, solving the problem of difficulty in determining the content of indole acetic acid during electrochemical detection. The current of the composite material increased by 22.7% after 200 cycles of redox reactions, demonstrating excellent stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118811818B_ABST
    Figure CN118811818B_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube / platinum-coated titanium carbide composite material and its preparation method and application, and belongs to the technical field of preparation of electrochemical sensor materials. The preparation method comprises the following steps: dispersing carbon nanotubes in mixed acid, magnetically stirring, and obtaining a carbon nanotube dispersion; adding potassium permanganate to the carbon nanotube dispersion and stirring, centrifugally washing to obtain a precipitate, dispersing the precipitate in deionized water and ultrasonically obtaining a suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface; ultrasonically mixing the carbon nanotube suspension with the titanium carbide dispersion, adding potassium chloroplatinate solution and adjusting the pH value, adding sodium borohydride, stirring and ultrasonically obtaining a suspension, and centrifugally filtering and drying to obtain a carbon nanotube platinum-coated titanium carbide composite material. When the composite material is used as a modified electrode material for the detection of indoleacetic acid, the problem of weak indoleacetic acid signal detected by the electrochemical sensor is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of electrochemical sensor materials, and specifically relates to a carbon nanotube / platinum-coated titanium carbide composite material and a preparation method and application thereof. Background Art

[0002] In recent years, a portable, compact and highly flexible screen-printed electrode (SPE) has been developed and successfully applied in electrochemical detection. SPE can be used with simple and portable electrochemical devices to perform rapid testing and on-site in-situ testing using various electrochemical methods. Plant hormones are generally divided into four categories: auxins, gibberellins, cytokinins, and inhibitors. Indoleacetic acid belongs to the auxin family, and studying the concentration of indoleacetic acid in plants is crucial for a deeper understanding of its biological effects. However, due to the low content of indoleacetic acid and the small amount of electroactive substances in SPE, it is difficult to measure, so it is necessary to establish an analytical method for detecting indoleacetic acid with a strong electrochemical signal.

[0003] In order to solve this problem, people have adopted a variety of methods to determine the indoleacetic acid in plants. The Chinese patent document with publication number CN111103282A discloses a method for detecting the indoleacetic acid content in Pleurotus ostreatus, which uses a spectrophotometer to measure and calculate the indoleacetic acid content. However, this detection method is relatively complicated, and the equipment is not easy to carry, so it is not the best method for detecting indoleacetic acid. Summary of the invention

[0004] The first purpose of the present invention is to provide a carbon nanotube / platinum-coated titanium carbide composite material with high conductivity and high stability; the second purpose is to provide a method for preparing the above material; the third purpose is to provide an application of the above material in the modification of screen-printed electrodes, which solves the problem that the indoleacetic acid content is difficult to measure during electrochemical detection.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a carbon nanotube / platinum-coated titanium carbide composite material, comprising the following steps:

[0007] (1) dispersing carbon nanotubes in a mixture of nitric acid and sulfuric acid, and stirring with a magnetic force to obtain a carbon nanotube dispersion;

[0008] (2) adding potassium permanganate to the carbon nanotube dispersion, stirring, centrifuging, washing, obtaining a precipitate, dispersing the precipitate in deionized water, and ultrasonicating to obtain a suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface;

[0009] (3) Ultrasonic mixing of a suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface and a dispersion of titanium carbide with hydroxyl and carboxyl groups grafted on the surface for 10 to 30 minutes, followed by adding a potassium chloroplatinate solution and adjusting the pH value with an alkaline solution, and then adding sodium borohydride, stirring and ultrasonicating to obtain a suspension, and then centrifuging, filtering, and drying to obtain a carbon nanotube / platinum-coated titanium carbide composite material.

[0010] Preferably, in step (1), the volume ratio of sulfuric acid to nitric acid is 20-30:1; the mass volume ratio of carbon nanotubes to mixed acid is 1-3 g:42-62 ml; and the magnetic stirring time is 2-6 h.

[0011] Preferably, in step (2), the mass volume ratio of potassium permanganate to carbon nanotube dispersion is 2-4 g:42-62 ml; the stirring time is 1-3 h, the ultrasonic time is 20-40 min; and the concentration of the carbon nanotube suspension is 2.0-4.0 mg / ml.

[0012] Preferably, in step (3), the concentration of the titanium carbide dispersion is 0.5-1.5 mg / ml, the concentration of the potassium chloroplatinate solution is 1 mM-3 mM; the volume ratio of the carbon nanotube suspension, the titanium carbide dispersion and the potassium chloroplatinate solution is 1:4-6:1.8-3.8, the mass volume ratio of sodium borohydride to the potassium chloroplatinate solution is 0.4-0.8 mg:1.8-3.8 ml; the alkali solution is sodium hydroxide solution or potassium hydroxide solution; the pH of the mixed solution is 7-9; the stirring time is 1-3 h, and the ultrasonic time is 0.5-1.5 h.

[0013] The method for preparing the carbon nanotube / platinum-coated titanium carbide composite material provided by the present invention comprises the following steps: in step (1) and step (2), the carbon nanotubes are dispersed in a mixed acid composed of sulfuric acid and nitric acid, and the carbon nanotubes are oxidized and melted at defects by the strong oxidizing property of the mixed acid, thereby enhancing the activity of the carbon nanotubes; and then, hydroxyl groups and carboxyl groups are grafted onto the surface of the carbon nanotubes by the strong oxidizing property of potassium permanganate, and the generated carboxyl groups and hydroxyl groups are used for bonding modification.

[0014] In a second aspect, the present invention provides a carbon nanotube / platinum-coated titanium carbide composite material prepared by the above method, wherein the composite material comprises titanium carbide nanosheets, carbon nanotubes uniformly loaded on the surface of the titanium carbide nanosheets, the titanium carbide nanosheets and the carbon nanotubes are connected by hydrogen bonds, platinum nanoparticles are uniformly loaded on the surface of the carbon nanotubes, and the composite material as a whole presents a three-dimensional conductive network structure; the surfaces of the titanium carbide nanosheets and the carbon nanotubes have hydroxyl groups and carboxyl groups.

[0015] Preferably, the mass ratio of the carbon nanotubes to the titanium carbide nanosheets is 1:1-2.25, and the content of the platinum nanoparticles is 8-14.6wt% of the composite material.

[0016] In a third aspect, the present invention provides an application of the above composite material, using the carbon nanotube / platinum-coated titanium carbide composite material for modifying screen-printed electrodes.

[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0018] 1. The technical solution of the present invention provides a carbon nanotube / platinum-coated titanium carbide composite material, including titanium carbide nanosheets, carbon nanotubes uniformly loaded on the surface of the titanium carbide nanosheets, and platinum nanoparticles uniformly loaded on the surface of the carbon nanotubes, so that the composite material as a whole presents a three-dimensional conductive network structure, which significantly enhances the conductivity of the material.

[0019] 2. The technical solution of the present invention, in the process of preparing the carbon nanotube / platinum-coated titanium carbide composite material, firstly, the carbon nanotubes are dispersed in a mixed acid composed of sulfuric acid and nitric acid, and the carbon nanotubes are oxidized and melted at the defects by the strong oxidizing property of the mixed acid, thereby enhancing the activity of the carbon nanotubes; then, by the strong oxidizing property of potassium permanganate, hydroxyl and carboxyl groups are grafted on the surface of the carbon nanotubes, thereby enhancing the dispersion ability and adhesion of the carbon nanotubes in the solution, and the surface of the titanium carbide nanosheets also has hydroxyl and carboxyl functional groups, and the carbon nanotubes and the titanium carbide nanosheets are connected by hydrogen bonds. After 200 cycles of redox reaction, the current of the obtained composite material not only did not decrease, but increased by 22.7%, indicating that the composite material has very excellent stability.

[0020] 3. The carbon nanotube / platinum-coated titanium carbide composite material prepared by the technical solution of the present invention is applied to the modification of screen-printed electrode sensors. Compared with the prior art, it can significantly improve the electrochemical signal and stability of the sensor and solve the problem of difficulty in determining the indoleacetic acid content during electrochemical detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 CNTs-Pt / Ti3C2T prepared in Example 1 x Scanning electron microscope (SEM) image of the composite material at 1 μm scale;

[0022] Figure 2 CNTs-Pt / Ti3C2T prepared in Example 1 x Scanning electron microscope (SEM) image of the composite material at 100nm scale;

[0023] Figure 3 CNTs-Pt / Ti3C2T prepared in Example 1 x Concentration optimization curve of composite materials in characterization solution;

[0024] Figure 4 CNTs-Pt / Ti3C2T prepared in Example 1x Concentration optimization curve of composite materials;

[0025] Figure 5 CNTs-Pt / Ti3C2T prepared in Example 1 x CV graph of composite material detecting indoleacetic acid;

[0026] Figure 6 CNTs-Pt / Ti3C2T prepared in Example 1 x Stable performance diagram of composite materials. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the examples and comparative examples, but the present invention is not limited thereto. The dispersion of titanium carbide with carboxyl and hydroxyl groups grafted on the surface used in the examples was obtained by commercially purchasing titanium carbide (Ti3C2T x ) MXene nanosheets (Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., 500 mg, purity about 74-81 wt%) were ultrasonically mixed with deionized water to prepare a dispersion of 0.5-1.5 mg / ml.

[0028] Example 1: Preparation of carbon nanotube / platinum-coated titanium carbide composite material CT-1

[0029] (1) dispersing 2 g of carbon nanotubes in a mixed acid of nitric acid and sulfuric acid, and magnetically stirring for 4 h to obtain a carbon nanotube dispersion; wherein the mixed acid is a mixed acid solution of 50 ml of sulfuric acid and 2 ml of nitric acid;

[0030] (2) adding 3 g of potassium permanganate to 52 ml of the carbon nanotube dispersion and stirring for 2 h, centrifuging and washing to obtain a precipitate, dispersing the precipitate in deionized water and ultrasonicating for 30 min to obtain a 3.0 mg / ml suspension of carbon nanotubes with surface grafted hydroxyl and carboxyl groups;

[0031] (3) 1 ml of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface was ultrasonically mixed with 5 ml of a dispersion of titanium carbide with 1.0 mg / ml of hydroxyl and carboxyl groups grafted on the surface for 20 min, followed by adding 2.8 ml of a 2 mM potassium chloroplatinate solution and adjusting the pH to 8 with an alkaline solution, and then adding 0.6 mg of sodium borohydride, stirring for 2 h and ultrasonicating for 1 h to obtain a suspension, and then centrifuging, filtering, and drying to obtain a carbon nanotube / platinum-coated titanium carbide composite material (CNTs-Pt / Ti3C2T x ), named as CT-1. The mass ratio of carbon nanotubes to titanium carbide nanosheets in CT-1 is 1:1.67, and the doping ratio of platinum nanoparticles is 11.2%.

[0032] Example 2: Preparation of carbon nanotube / platinum-coated titanium carbide composite material CT-2

[0033] (1) Dispersing 1 g of carbon nanotubes in a mixed acid of nitric acid and sulfuric acid, and stirring magnetically for 2 h to obtain a carbon nanotube dispersion. The mixed acid is a mixed acid solution of 40 ml of sulfuric acid and 2 ml of nitric acid;

[0034] (2) adding 2 g of potassium permanganate to 42 ml of the carbon nanotube dispersion and stirring for 1 h, centrifuging and washing to obtain a precipitate, dispersing the precipitate in deionized water and ultrasonicating for 20 min to obtain a 2.0 mg / ml suspension of carbon nanotubes with surface grafted hydroxyl and carboxyl groups;

[0035] (3) 1 ml of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface was ultrasonically mixed with 4 ml of a dispersion of titanium carbide with 0.5 mg / ml of hydroxyl and carboxyl groups grafted on the surface for 10 min, followed by adding 1.8 ml of a 1 mM potassium chloroplatinate solution and adjusting the pH to 7 with an alkaline solution, and then adding 0.4 mg of sodium borohydride, stirring for 1 h and ultrasonicating for 0.5 h to obtain a suspension, and then centrifuging, filtering, and drying to obtain a carbon nanotube / platinum-coated titanium carbide composite material (CNTs-Pt / Ti3C2T x ), named as CT-2. The mass ratio of carbon nanotubes to titanium carbide nanosheets in CT-2 is 1:1, and the doping ratio of platinum nanoparticles is 8%.

[0036] Example 3: Preparation of carbon nanotube / platinum-coated titanium carbide composite material CT-3

[0037] (1) Dispersing 3 g of carbon nanotubes in a mixed acid of nitric acid and sulfuric acid, and stirring magnetically for 6 h to obtain a carbon nanotube dispersion. The mixed acid is a mixed acid solution of 60 ml of sulfuric acid and 2 ml of nitric acid;

[0038] (2) adding 4 g of potassium permanganate to 62 ml of the carbon nanotube dispersion and stirring for 3 h, centrifuging and washing to obtain a precipitate, dispersing the precipitate in deionized water and ultrasonicating for 40 min to obtain a 4.0 mg / ml suspension of carbon nanotubes with surface grafted hydroxyl and carboxyl groups;

[0039] (3) 1 ml of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface was ultrasonically mixed with 6 ml of a dispersion of titanium carbide with 1.5 mg / ml of hydroxyl and carboxyl groups grafted on the surface for 30 min, followed by adding 3.8 ml of a 3 mM potassium chloroplatinate solution and adjusting the pH to 9 with an alkaline solution, and then adding 0.8 mg of sodium borohydride, stirring for 3 h and ultrasonicating for 1.5 h to obtain a suspension, and then centrifuging, filtering, and drying to obtain a carbon nanotube / platinum-coated titanium carbide composite material (CNTs-Pt / Ti3C2T x ), named as CT-3. The mass ratio of carbon nanotubes to titanium carbide nanosheets in the CT-3 is 1:2.25, and the doping ratio of platinum nanoparticles is 14.6%.

[0040] Comparative Example 1: Preparation of carbon nanotube / platinum-coated titanium carbide composite material CT-4

[0041] 1 ml of 3.0 mg / ml carbon nanotube suspension was ultrasonically mixed with 5 ml of 1.0 mg / ml titanium carbide dispersion with hydroxyl and carboxyl groups grafted on the surface for 20 min, then 2.8 ml of 2 mM potassium chloroplatinate solution was added and adjusted to pH 8 with an alkaline solution, and then 0.6 mg of sodium borohydride was added, stirred for 2 h and ultrasonicated for 1 h to obtain a suspension, and then centrifuged, filtered, and dried to obtain a carbon nanotube / platinum-coated titanium carbide composite material (CNTs-Pt / Ti3C2T x ), named CT-4. The mass ratio of carbon nanotubes to titanium carbide nanosheets in CT-4 is 1:1.67, and the doping ratio of platinum nanoparticles is 11.2%.

[0042] Comparative Example 2: Preparation of carbon nanotube / platinum-coated titanium carbide composite material CT-5

[0043] (1) dispersing 2 g of carbon nanotubes in a mixed acid of nitric acid and sulfuric acid, and magnetically stirring for 4 h to obtain a carbon nanotube dispersion; wherein the mixed acid is a mixed acid solution of 50 ml of sulfuric acid and 2 ml of nitric acid;

[0044] (2) adding 3 g of potassium permanganate to 52 ml of the carbon nanotube dispersion and stirring for 2 h, centrifuging and washing to obtain a precipitate, dispersing the precipitate in deionized water and ultrasonicating for 30 min to obtain a 3.0 mg / ml suspension of carbon nanotubes with surface grafted hydroxyl and carboxyl groups;

[0045] (3) 1 ml of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface was ultrasonically mixed with 5 ml of 1.0 mg / ml titanium aluminum carbon (Ti3AlC2) dispersion for 20 min, followed by adding 2.8 ml of 2 mM potassium chloroplatinate solution and adjusting the pH to 8 with an alkaline solution, and then adding 0.6 mg of sodium borohydride, stirring for 2 h and ultrasonicating for 1 h to obtain a suspension, which was centrifuged, filtered, and dried to obtain a carbon nanotube / platinum-coated titanium carbide composite material (CNTs-Pt / Ti3AlC2), named CT-5. The mass ratio of carbon nanotubes to titanium carbide nanosheets in the CT-5 was 1:1.67, and the doping ratio of platinum nanoparticles was 11.2%.

[0046] Test Example 1

[0047] The CT-1 composite material prepared in Example 1 was subjected to morphology (SEM) test and electrochemical test.

[0048] The carbon nanotube / platinum-coated titanium carbide composite material obtained in Example 1 was subjected to SEM testing, and the results are shown in Figure 1 and Figure 2 .from Figure 1 It can be seen that the surface of titanium carbide layered nanomaterials is tightly bound to carbon nanotubes. This is because after acid treatment, a large number of hydroxyl and carboxyl functional groups are attached to the surface of the modified carbon nanotubes. Therefore, when the carbon nanotubes and titanium carbide nanosheets are mixed, hydrogen bonds are formed between the two, and the combination is very tight. In addition, the surface of carbon nanotubes is evenly loaded with platinum nanoparticles, indicating that platinum has been successfully reduced from potassium chloroplatinate. Figure 2 The distribution relationship between platinum nanoparticles, carbon nanotubes and titanium carbide nanosheets is more clearly revealed. In the figure, we can see that the surface of titanium carbide nanosheets is evenly loaded with carbon nanotubes, and the surface of carbon nanotubes is evenly loaded with platinum nanoparticles. The composite material as a whole presents a three-dimensional conductive network structure. This structure not only enhances the conductivity of the material but also improves the stability of the material in harsh environments.

[0049] By scanning the cyclic voltammetry of carbon nanotube / platinum-coated titanium carbide composite materials in the characterization solution, such as Figure 3 The current of carbon nanotube / platinum coated titanium carbide composite materials with different concentrations of 0.5mg / ml, 1.0mg / ml, 1.5mg / ml and 2.0mg / ml was compared and found ( Figure 4 ), the electrochemical signal of the carbon nanotube / platinum-coated titanium carbide composite material was the highest at 1.5 mg / ml, so the concentration of 1.5 mg / ml was used in the next experiment.

[0050] Application Example 1

[0051] The materials obtained in the above examples and comparative examples were used for the detection of indoleacetic acid, and the steps were as follows:

[0052] (1) dispersing the prepared material in deionized water to obtain a 1.5 mg / ml carbon nanotube / platinum-coated titanium carbide composite material dispersion;

[0053] (2) A 1.5 mg / ml dispersion of carbon nanotubes / platinum-coated titanium carbide composite material was modified on the surface of the screen-printed electrode by drop coating and dried in a fume hood to obtain CNTs-Pt / Ti3C2T x / SPE modified electrode;

[0054] (3) 4×10 -5 mol / L indoleacetic acid was dropped on CNTs-Pt / Ti3C2T x The electrode surface was modified with / SPE and scanned by cyclic voltammetry.

[0055] The scanning parameters were set as follows: 0.7~-0.3V range potential, scanning speed 0.1V / s, scanning number 4, interval 0.001V, sensitivity 1.0×10 -4 A / V.

[0056] The experimental results are shown in Table 1:

[0057]

[0058] The bare SPE electrode and CNTs-Pt / Ti3C2T x / SPE modified electrodes in the simultaneous detection of indoleacetic acid electrochemical signals ( Figure 5 The bare SPE electrode did not show redox peaks due to the low indoleacetic acid content. x The SPE modified by the composite material benefits from the excellent assembly and synergistic effect between carbon nanotubes and titanium carbide nanosheets. The carbon nanotube / titanium carbide composite material exhibits excellent electrochemical performance. Positive or negative groups can be grafted on the surface of titanium carbide and carbon nanotubes to prevent agglomeration. By adding carbon nanotubes, the disordered accumulation of titanium carbide nanosheets is effectively suppressed, which creates sufficient space for the adsorption of indoleacetic acid molecules and further promotes the transfer of electrons. At the same time, after titanium carbide is combined with metal platinum, the electron transfer is faster and more efficient, thereby improving the reaction efficiency. Therefore, CNTs-Pt / Ti3C2T x / SPE conductivity is greatly enhanced, and its indoleacetic acid detection signal is very obvious, with a redox peak current of 33μA.

[0059] As can be seen from Table 1, since the carbon nanotubes of CT-4 are not grafted with hydroxyl and carboxyl groups, and the surface of the titanium aluminum carbon material of CT-5 does not contain hydroxyl and carboxyl groups, the currents of the two when detecting indoleacetic acid are significantly lower than those of CT-1~CT-3, which indicates that their conductivity is low; and their stability is also relatively poor, which indicates that hydroxyl and carboxyl groups are very important for the combination of carbon nanotubes and titanium carbide, and affect the electrochemical ability of the composite material.

[0060] For CNTs-Pt / Ti3C2T x / SPE stability was tested and CNTs-Pt / Ti3C2T x When the SPE modified electrode was used to detect indoleacetic acid, it was found that after 200 consecutive scans ( Figure 6 ), the composite material still maintained high activity, and the current increased by 22.7% compared with the first cycle. This shows that CNTs-Pt / Ti3C2T x Composite materials have excellent stability.

[0061] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanotube / platinum-coated titanium carbide composite material, characterized in that: The following steps are involved: (1) dispersing carbon nanotubes in a mixture of nitric acid and sulfuric acid, and stirring with a magnetic force to obtain a carbon nanotube dispersion; (2) adding potassium permanganate to the carbon nanotube dispersion, stirring, centrifuging, washing, obtaining a precipitate, dispersing the precipitate in deionized water, and ultrasonicating to obtain a suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface; (3) ultrasonically mixing the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface with the dispersion of titanium carbide with hydroxyl and carboxyl groups grafted on the surface for 10 to 30 minutes, then adding potassium chloroplatinate solution and adjusting the pH value with an alkaline solution, then adding sodium borohydride, stirring and ultrasonically obtaining a suspension, and obtaining a carbon nanotube / platinum-coated titanium carbide composite material through centrifugation, filtration and drying; In the step (2), the mass volume ratio of potassium permanganate to carbon nanotube dispersion is 2-4 g:42-62 ml; the stirring time is 1-3 h, and the ultrasonic time is 20-40 min; the concentration of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface is 2.0-4.0 mg / ml; In the step (3), the concentration of the dispersion of titanium carbide with hydroxyl and carboxyl groups grafted on the surface is 0.5-1.5 mg / ml, and the concentration of the potassium chloroplatinate solution is 1 mM-3 mM; the volume ratio of the suspension of carbon nanotubes with hydroxyl and carboxyl groups grafted on the surface, the dispersion of titanium carbide with hydroxyl and carboxyl groups grafted on the surface, and the potassium chloroplatinate solution is 1:4-6:1.8-3.8, and the mass volume ratio of sodium borohydride to potassium chloroplatinate solution is 0.4-0.8 mg:1.8-3.8 ml; the alkali solution is sodium hydroxide solution or potassium hydroxide solution; the pH value is 7-9; the stirring time is 1-3 h, and the ultrasonic time is 0.5-1.5 h.

2. The method for preparing the carbon nanotube / platinum-coated titanium carbide composite material according to claim 1, characterized in that: In the step (1), the volume ratio of sulfuric acid to nitric acid is 20-30:1; the mass volume ratio of carbon nanotubes to mixed acid is 1-3 g:42-62 ml; and the magnetic stirring time is 2-6 h.

3. A carbon nanotube / platinum-coated titanium carbide composite material, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1 to 2.

4. The carbon nanotube / platinum-coated titanium carbide composite material according to claim 3, characterized in that: The composite material comprises titanium carbide nanosheets, carbon nanotubes are uniformly loaded on the surface of the titanium carbide nanosheets, platinum nanoparticles are uniformly loaded on the surface of the carbon nanotubes, and the composite material as a whole presents a three-dimensional conductive network structure; the mass ratio of the carbon nanotubes to the titanium carbide nanosheets is 1:1-2.25, and the content of the platinum nanoparticles is 8-14.6wt% of the composite material.

5. An application of the carbon nanotube / platinum-coated titanium carbide composite material as claimed in claim 3 or 4, characterized in that: The carbon nanotube / platinum-coated titanium carbide composite material is used for modifying screen-printed electrodes.

Citation Information

Patent Citations

  • Method for detecting content of indoleacetic acid in oyster mushrooms

    CN111103282A